Topical issues of administrative and legal support of the establishment and activities of science and technology museums - Юринець, Юлія Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The features of the functioning of science and technology museums in Ukraine and abroad. It is shown thatthe absence of adequate government support creates difficulties for the operation of technical museums that have typically departmental in nature. The measures of the legislative and fiscal support.